Utilization of Vermiculite for Solving Hematite Sagging in Water-Based Drilling Fluids. (30th September 2022) - Basfar, Salem; Ahmed, Ashraf; Elkatatny, Salaheldin
Abstract : The sagging phenomenon of solids, such as hematite, in drilling fluids is commonly experienced when drilling at elevated temperature conditions presenting operational and well control issues. Thus, we report herein the addition of vermiculite to water-based drilling fluid with the objective of improving fluid stability by hematite sagging mitigation. Different quantities of vermiculite clay (3–6 lb/bbl) were used and the sagging tendency was evaluated for the base and vermiculite-containing drilling fluids under static and dynamic conditions. From the sag measurements, the optimum vermiculite content was determined, and the influence on the key drilling fluid properties was studied by conducting the rheology, viscoelasticity, filtration, density, and alkalinity measurements. To simulate the practical elevated temperature, the tests were performed at temperature up to 250°F. The outcomes of this study revealed that the addition of vermiculite to the base drilling fluid significantly improved fluid stability. The content of 5 lb/bbl vermiculite was sufficient to mitigate the hematite sagging at elevated temperatures and drive the sag tendency factors to safe values. The ability of vermiculite to improve fluid stability was confirmed with the enhancement of rheological and viscoelastic properties, since the recommended vermiculite content resulted in a 24% reduction in plastic viscosity, 9% increment on yield point, and improved storage and loss modulus with better gelling structure. Also, the filtration properties were improved with 5 lb/bbl vermiculite, as the filtrated volume was reduced from 6.2 to 5 cm 3 and formulated a preferred filter cake with less weight and thickness. In addition, the small amount of vermiculite did not change the drilling fluid weight, and the pH was slightly dropped but within the practical alkalinity range.